Quality of Life of Children age from (8- lessthan13) years with Acute Lymphocytic Leukemia Undergoing Chemotherapy at Hematology Center in Medical City - qasim, asmahan (Iraqi National Journal of Nursing Specialties, 2022)
Objective (s): To assess the QoL of children age from (8- lessthan13) years with acute lymphocytic leukemia undergoing chemotherapy and to find out the relationship between the QoL of children with acute lymphocytic leukemia and their illness history.Methodology:  A descriptive study included (40) children with acute lymphocytic leukemia who were ranged between (8 - less than 13 years) at the Hematology Center in Medical City for the period from 4th March 2021 to 1st September 2021. The sample was non-probability (purposive) sample of children (male and female). A questionnaire designed with 2 main parts was used. The first part focused on sociodemographic characteristic for children. The second part, which consisted of four domains, focused on the quality of children with acute lymphocytic leukemia. The data were analyzed by applying statistical methods (descriptive and inferential) that were applied by using SPSS version 20.Results: The study's findings that children aged from 8 to less than 13 years have moderate effects on all domains of the quality of life in which 90% of them are showing a moderate level in the physical functioning domain,70% are showing a moderate level in the emotional functioning domain, in regard to the social functioning domain 52.5% are showing a moderate level and 67.5% of them are showing a moderate level in school functioning domain.Conclusion: According to the finding of the present study, the researchers concludes that acute lymphocytic leukemia is more prevalent in males than females.  In children aged 8 to less than 13 years, all domains of quality of life are moderately affected.Recommendations:  The study recommended that all children with ALL and their parents get counseling and education programs about leukemia, medical care, efforts to overcome side effects, and nutrition, all of which help to improve the children's quality of life.